Respons Pertumbuhan dan Produksi Bawang Daun (Allium fistulosum L.) pada Berbagai Dosis Kompos Ampas Sagu di dalam Polibag - Hofni L. Watopa; Besse Amriati; Inna M. Rumainum; Budiyono; Antonius Suparno (Fakultas Pertanian Universitas Papua, 2020)
This study aimed to examine the growth and production response of Allium fistolosum to the application of various doses of sago dregs compost and to determine the appropriate dose of sago dregs compost for it cultivation in polybags. This research was designed in Randomized Block Design (RAK) consisting of 4 doses of sago dregs compost treatments. The results showed that different doses of sago dregs compost had a significant effect on the growth and yield of Allium fistolosum. The dose of sago dregs compost with a dose of 600 g gave the highest yield on the parameters of observing plant height, stem diameter, and plant fresh weight.